Sound lateralisation in patients with left or right cerebral hemispheric lesions: relation with unilateral visuospatial neglect - Tanaka, H. (BMJ Group, 1999)
OBJECTIVES—To localise the brain lesion that causes disturbances of sound lateralisation and to examine the correlation between such deficit and unilateral visuospatial neglect. METHOD—There were 29 patients with right brain damage, 15 patients with left brain damage, and 22 healthy controls, who had normal auditory and binaural thresholds. A device was used that delivered sound to the left and right ears with an interaural time difference using headphones. The amplitude (an index of ability to detect sound image shifts from the centre) and midpoint (an index of deviation of the interaural time difference range perceived as the centre) parameters of interaural time difference were analysed in each subject using 10 consecutive stable saw toothed waves. RESULTS—The amplitude of interaural time difference was significantly higher in patients with right brain damage than in controls. The midpoint of the interaural time difference was significantly more deviated in patients with right brain damage than in those with left brain damage and controls (p<0.05). Patients with right brain damage with lesions affecting both the parietal lobe and auditory pathway showed a significantly higher amplitude and deviated midpoint than the controls, whereas right brain damage with involvement of only the parietal lobe showed a midpoint significantly deviated from the controls (p<0.05). Abnormal sound lateralisation correlated with unilateral visuospatial neglect (p<0.05). CONCLUSIONS—The right parietal lobe plays an important part in sound lateralisation. Sound lateralisation is also influenced by lesions of the right auditory pathway, although the effect of such lesions is less than that of the right parietal lobe. Disturbances of sound lateralisation correlate with unilateral visuospatial neglect.